Post‐coronavirus disease 2019 organizing pneumonia confirmed pathologically by video‐assisted thoracoscopic surgery. Issue 12 (28th October 2021) - Sugino, Keishi; Ono, Hirotaka; Haraguchi, Shuji; Igarashi, Seiji; Hebisawa, Akira; Tsuboi, Eiyasu
Abstract: Coronavirus disease 2019 (COVID‐19), caused by severe acute respiratory syndrome coronavirus 2, has become a global pandemic. Many survivors of serious COVID‐19 pneumonia have long‐term residual pulmonary disease. However, there is little documentation of the histopathological characteristics of lung sequelae post‐COVID‐19 and effective treatments. We present two Japanese cases of lung sequelae post‐COVID‐19. The patients were histopathologically diagnosed with organizing pneumonia (OP) or OP with fibrosis and no diffuse alveolar damage on video‐assisted thoracoscopic surgery. Case 1, who had been diagnosed with OP, was successfully treated with corticosteroid and other immunosuppressive agents over a 6‐month period. Although case 2, who had been diagnosed with OP with fibrosis, had a partial and unsatisfactory response to immunosuppressive agents, the patient responded to antifibrotic treatment including nintedanib. Abstract : We present two Japanese cases of lung sequelae post coronavirus disease 2019 (COVID‐19). The patients were histopathologically diagnosed with organizing pneumonia (OP) or OP with fibrosis and no diffuse alveolar damage on video‐assisted thoracoscopic surgery. Case 1, who was diagnosed with OP, was successfully treated with corticosteroid and other immunosuppressive agents over a 6‐month period. Although case 2, who was diagnosed with OP with fibrosis, had a partial and unsatisfactory response to immunosuppressive agents, the patient responded to antifibrotic treatment including nintedanib.